MARKETING PUBLIC RELATIONS STRATEGY IN WEDDING PARTY EVENTS AT HORISON HOTEL BEKASI - Pratama, Rismandha Kusuma; Anggraini, Rosita (Transpublika Publisher, 2024)
Currently, hotel services do not stop at providing the best rooms, but also include a variety of experiences, one of which is the wedding party event service as a special event. However, with the Covid- 19 pandemic, the hotel business had to re-think so that the business could run and survive. One of the hotels that has been able to survive the pandemic that also offers wedding party event services is the Horison Ultima Bekasi hotel. The purpose of this study was to determine the marketing public relations strategy in the wedding party event at the Horison Bekasi hotel. The theory used in this study is the marketing public relations strategy of Thomas L. Harris which consists of a pull, push, and pass strategy. This research approach is qualitative. This type of research is descriptive. Information obtained from 4 informants. Data collection techniques through interviews, observation, and documentation. Data analysis techniques through the stages of data reduction, data presentation, drawing conclusions, and data verification. The results of the study show that the Horison Bekasi hotel uses conventional media and social media for publicity as a pull strategy, improving service quality and promos as a push strategy, as well as maintaining good relations with consumers and customer testimonials as a pass strategy. This is in accordance with the MPR strategy model put forward by Thomas L. Harris, namely the pull, push, and pass strategy.